The influence of nitrogen on the deformation behaviour of a modified AISI type 200 series alloy - Biggs, Taryn (Centre for Materials Engineering, 2016)
This thesis investigates the influence of nitrogen concentration on the deformation behaviour of a modified AISI 200 type alloy. The Fe-18Cr-4Ni-7Mn base alloys contained a range of nitrogen contents from 0 to 0.27 wt%. The tensile behaviour was characterised by uniaxial tensile testing. The room temperature yield strength was shown to decrease with increasing nitrogen content for nitrogen contents less than 0.1 wt%. This decrease was attributed to the presence of secondary phases in the annealed state. An increase in yield strength was observed with further additions of nitrogen and this is probably due to solid solution strengthening and a Cottrell interaction. The variation of room temperature ultimate tensile strength showed no dependence on nitrogen content. Elevated temperature tensile tests (120DC) showed an increase in ultimate tensile strength and yield strength with nitrogen content suggesting that solid solution strengthening and a Cottrell interaction are occurring in this alloy range. Room temperature deformation was shown to induce a transformation from austenite to martensite throughout this alloy range, the degree of transformation decreasing with increasing nitrogen content. This transformation was shown to provide considerable strengthening and work hardening to the alloy. The low stacking fault energy (SFE) of this alloy range ensured that cross-slip was significantly inhibited during room temperature deformation and the deformation mode was observed to be planar glide. Nitrogen was shown to increase the SFE of this alloy range thus causing a decrease in the inhibition of cross-slip with increasing nitrogen content. Increasing the nitrogen content thus causes a decrease in strength if the contributions of a deformation-induced transformation, SFE variation and secondary phases are considered but causes an increased strengthening contribution due to solid solution strengthening and a Cottrell interaction. Hence as the nitrogen content increases different strengthening mechanisms are activated and no overall trend of room temperature ultimate tensile strength with nitrogen content is observed. The ductility and formability of the steels did not appear to show any distinct trends with changes in nitrogen content.